The Development of Digital Pocketbook Based on the Ethnoscience of the Singkawang City to Increase Students' Scientific Literacy on Heat Matter and Its Transfer - Emi Sulistri; Eti Sunarsih; Erdi Guna Utama; Usinah Robert Moseki (JETL (Journal of Education, Teaching and Learning), 2020)
Many factors cause low student scientific literacy, one of which is due to the inappropriate use of the selected learning media in the learning process. This study aims to produce ethnoscience-based digital pocketbooks that are feasible and attractive to use by students and are effective in improving students' scientific literacy. The ADDIE model research procedure used includes five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The sample consisted of 141 fifth grade students in three Singkawang City Public Elementary Schools. Data collection techniques in the form of interviews, validation, questionnaires, and scientific literacy tests. Based on the results of the analysis stage, it was found that the KI and KD were related to cultural elements and local wisdom of the city of Singkawang. The design stage is obtained by designing a book framework, presentation of material, instruments. The development stage obtained material, graphic, and linguistic feasibility. Phase I validation was 3.25 with a percentage of 81.41% and stage II was 3.72 with an eligibility percentage of 92.92%. The results of the practitioner validator were 3.8 with a percentage of 95% and were classified as valid. Implementation stage, validation of the attractiveness of student and student responses to linguistic aspects of 3.31 and 3.46, respectively. While the material and graphic aspects of the student's response have a value of 3.23 and 3.22 respectively in the attractive criteria and student responses have a value of 3.33 and 3.39 respectively in the very interesting category. This means that ethnoscience-based digital pocketbooks are generally feasible, easy to understand, and interesting to use because they have a new display concept that is coherently integrated with local culture and a design that is in line with developments. Students' scientific literacy skills increased with an effect size value of 0.621 with moderate criteria at 73% presentation. It can be concluded that ethnoscience-based digital pocketbooks can effectively improve students' scientific literacy skills.